PSM FAKULTAS TEKNIK UNDIP: Studi Terhadap Faktor-Faktor yang Mempengaruhi Eksistensi Paduan Suara Mahasiswa Teknik Universitas Diponegoro Semarang - Mujianto, Gracia Destari; Raharjo, Eko (Universitas Negeri Semarang, 2019)
Paduan Suara Mahasiswa Teknik (PSMT) is a student choir that was established in 2003 with various achievements they gained all of this time. The aim of this study is to know and to explain the factors that influence the existence of Diponegoro University Engineering Student Choir and their efforts to maintain their existence. This research is using qualitative method with descriptive approach. Data is obtained from interviews, observations, and documentation. Data analysis techniques used were data collection; data reduction; data display; conclusion and verification. The results showed that the factors that are influencing the existence of Engineering Student Choir of Undip were their activities as well as having facts that were applied through achievements, group programs, group effectiveness, and also the election of new members. Undip Engineering Student Choir’s effort to maintain their existence is by having innovations to strengthen the brand of PSMT Undip by participating in competitions, holding concerts, and regeneration of memberships.